Petrography study on potential rare earth element (REE)-bearing minerals in igneous rocks from Sabah, Malaysia - Ling, Sin Yi; Darmesah Gabda; Kim Kyoung-Woong; Baba Musta (Faculty of Science & Natural Resources, UMS, 2024)
This paper presents a petrographic study on potential Rare Earth Element (REE)-bearing minerals found in various igneous rocks from Sabah. By employing advanced polarising microscopy techniques, this study identified and characterized the mineralogical composition and texture of possible REE-bearing phases within peridotite, basalt, serpentinite, andesite, diorite and dacite. The petrographic observations provided critical insights into the possible mineralization of REEs, including lanthanides, yttrium (Y) and scandium (Sc). Several accessory minerals that are commonly associated with REEs, such as monazite, apatite, chromite-spinel, magnetite and zircon were identified. The abundance and composition of these potential REE carriers varied significantly across different geological settings, highlighting the importance of local geological context in REE mineralization and distribution patterns. The present study indicated that basalt contained the overall most significant presence of REE-bearing minerals which exhibited the highest potential for REE mineralization. These findings also suggested that the REE enrichment in these rocks were closely associated with their magmatic origin and later potential hydrothermal alteration processes which influenced the distribution of REE-bearing minerals. Therefore, this paper serves as a preliminary study for the identification of potential REE-bearing minerals in the igneous rocks which offers valuable information for future economic mineral exploration. The paper also suggests the need for further detailed geochemical analysis to determine the REE pathway in this region and to assess their economic viability for possible REE extraction in Sabah.